How to make a midbrain dopaminergic neuron - Arenas, Ernest; Denham, Mark; Villaescusa, J Carlos (Development (Cambridge, England), 2015)
Midbrain dopaminergic (mDA) neuron development has been an intense area of research during recent years. This is due in part to a growing interest in regenerative medicine and the hope that treatment for diseases affecting mDA neurons, such as Parkinson's disease (PD), might be facilitated by a better understanding of how these neurons are specified, differentiated and maintained in vivo. This knowledge might help to instruct efforts to generate mDA neurons in vitro, which holds promise not only for cell replacement therapy, but also for disease modeling and drug discovery. In this Primer, we will focus on recent developments in understanding the molecular mechanisms that regulate the development of mDA neurons in vivo, and how they have been used to generate human mDA neurons in vitro from pluripotent stem cells or from somatic cells via direct reprogramming. Current challenges and future avenues in the development of a regenerative medicine for PD will be identified and discussed.
Keywords: Dopaminergic Neurons; rozvržení tělního plánu; dopaminergní neurony; Parkinson's disease; vývojová regulace genové exprese; Stem cells; Regeneration; Body Patterning; Midbrain; Gene Expression Regulation, Developmental; Mesencephalon; Models, Biological; neurogeneze; zvířata; Humans; mezencefalon; Neurogenesis; biologické modely; Dopamine neurons; lidé; Reprogramming; Animals